Functionalized 3H-1, 2, 3, 4-triazaphosphole derivatives: Synthesis and structural characterization of novel low-coordinate phosphorus heterocycles. (3rd March 2016) - Sklorz, Julian A. W.; Schnucklake, Maike; Kirste, Matthias; Weber, Manuela; Wiecko, Jelena; Müller, Christian
GRAPHICAL ABSTRACT: ABSTRACT: The synthesis of novel functionalized 3 H -1, 2, 3, 4-triazaphosphole derivatives is presented, making use of the modular [3+2] dipolar cycloaddition reaction between an azide and a phosphaalkyne. These low-coordinate phosphorus heterocycles were prepared in high yield and could be characterized crystallographically. This strategy provides the possibility to access hitherto unknown chelating and potentially chiral P^O ligands based on triazaphospholes.